Diagnostic value of tumor-associated autoantibodies panel in combination with traditional tumor markers for lung cancer - Xu, Yu; Zhang, Wenjing; Xia, Tingting; Liu, Yuliang; Bi, Zhoukui; Guo, Liang; Xie, Weijia; Xiang, Ying; Xu, Zhi; Yu, Zubin; Li, Yafei; Bai, Li (Frontiers in Oncology, 2023)
The diagnostic value of 7 tumor-associated autoantibodies (AABs) including p53, PGP9.5, SOX2, GAGE7, GBU4-5, MEGEA1, and CAGE for the detection of lung cancer has shown in consistency in several studies. This study aimed to confirm the diagnostic value of 7AABs and to explore whether the diagnostic value would be improved by combining them with 7 traditional tumor-associated antigens (CEA, NSE, CA125, SCC, CA15-3, pro-GRP, and CYFRA21-1) in clinical settings. The plasma levels of 7-AABs were detected by enzyme-linked immunosorbent assay (ELISA) in 533 lung cancer cases and 454 controls. The 7 tumor antigens (7-TAs) were measured by Electrochemiluminescence immunoassay with Cobas 6000 (Roche, Basel, Switzerland). The positive rate of 7-AABs in the lung cancer group (64.00%) was significantly higher than that of healthy controls (47.90%). The 7-AABs panel was able to discriminate lung cancer from controls with a specificity of 51.50%. After combining the 7-AABs with 7-TAs, the sensitivity showed a significantly enhancement compared with 7AABs panel alone (92.09% vs 63.21%). In patients with early-stage lung cancer, the combination of 7-AABs and 7-TAs improved the sensitivity from 63.52% to 97.42%. In conclusion, our study found that the diagnostic value of 7-AABs was enhanced when combined with 7-TAs. This combined panel could be used as promising biomarker to detect early-stage lung cancer in clinical settings.